Bullying, school violence, and climate in evolving contexts culture, organization, and time - Astor, Ron Avi; Benbenîštî, Rāmî (Oxford University Press, 2019)
"This book outlines a novel unifying model that brings together these previously distinct literatures. We present an ecological model of school violence, bullying and safety in evolving contexts, to integrate all we have learned in the last decade, and suggest ways to move forward"...
Includes bibliographical references and index
Keywords: Bullying in schools; School violence; Harassment in schools; Aggressivität; Cyber-Mobbing; Mobbing; Gewalttätigkeit